Kearifan Lokal ”Kabus” dalam Perlindungan Sumberdaya Alam: Studi Suku Beser Betew di Kampung Tolobi Distrik Kofiau Kabupaten Raja Ampat - Maruapey, Azis; Kamaluddin, Kamaluddin; Lestaluhu, Rajab; Saeni, Fajrianto; Saeni, Agil (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
Kabus in Kofiau, Raja Ampat Regency is a traditional tradition that aims to preserve natural resources in the form of forests and seas. This Kabus has long been initiated by indigenous communities and religious leaders, and is supported by the local government and The Nature Conservancy (TNC). This research was conducted on the "kabus" system that has been implemented by the local community in Tolobi Village, Kofiau District, Raja Ampat Regency. This research was conducted for ± 1 month, namely during August 2024. The method in this research uses a descriptive method through observation sub-methods accompanied by interviews using the Focus Group Discussion (PGD) method. The results of this research show that local wisdom "kabus" in protecting natural resources is a traditional conservation model that was born from traditional knowledge a long time ago. "Kabus" is a form of "moratorium" on the extraction of natural resources in a certain period of time. Kabus is also a temporary stoppage of natural resource extraction activities so that they can grow and reproduce well through the implementation of an open-close system.